Promoting public health using competition law: applying the essential facilities doctrine to increase access to drugs in South Africa - Ntambirweki, Barbara (Department of Commercial Law, 2026)
The impact and nature of HIV/ AIDS pandemic epitomizes the greatest threat to public health and the most important challenge facing South Africa today. In 2007, it was estimated that more than five million people are living with HIV/ AIDS in South Africa which represents the highest number of sufferers in any country in the world. It is likely that close to 400,000 South Africans die of the disease each year. Despite this reality, the government for sometime was reluctant to deal with urgency and commitment required by the epidemic. After many years of controversy with civil society, the government fina11y adopted a new National HIV/ AIDS & STI Strategic Plan for South Africa 2007-11 (NSP). The primary aims of the NSP is to reduce the rate HIV infections by 50% by 2011 and reduce the impact of AIDS by expanding access to appropriate treatment care and support to 80% of those in need by 2011. The four priority areas of NSP include prevention, treatment, care, support; research monitoring and surveillance. Inspite of the efforts by the South African government, a number of obstacles continue to hinder the realization of access to affordable health treatment. One of the major causes for the overwhelming low rate of access is drug prices6. The drug prices are set by pharmaceutical companies that have invested money into research and development that leads to medical discoveries.In order to recover research and development expenditures, the pharmaceutical companies patent their ideas to exclude other manufacturers from cheaply producing and profiting from their inventions. Therefore, international trade regimes seek to guarantee that certain minimum standards are adopted for protection of intellectual property rights. Thus pharmaceutical patents as a major impediment to accessing affordable medicine will be discussed below.